Efficacy and safety of cinacalcet and active vitamin D in the treatment of secondary hyperparathyroidism in patients with chronic kidney disease: a network meta-analysis - Ni, Li-Hua; Yuan, Cheng; Song, Kai-Yun; Wang, Xiao-Chen; Chen, Si-Jie; Wang, Li-Ting; Zhang, Yu-Xia; Liu, Hong; Liu, Bi-Cheng; Tang, Ri-Ning (Annals of Translational Medicine, 2019)
Background: We conducted a network meta-analysis (NMA) to evaluate the efficacy and safety of cinacalcet, active vitamin D and cinacalcet plus active vitamin D in the treatment of secondary hyperparathyroidism (SHPT) in patients with chronic kidney disease (CKD). Methods: A systematic literature search was performed using the Cochrane Library, PubMed, EMBASE, Web of Science, Google Scholar, China National Knowledge Internet (CNKI) and Wanfang databases. In total, eight randomized controlled trials (RCTs) with 1,443 patients were eligible for this meta-analysis. Pairwise meta-analysis was performed to evaluate the compliance of intact parathyroid hormone (iPTH), Ca, P, etc., and the mortality and safety of cinacalcet plus active vitamin D and active vitamin D alone. Then, NMA was used to estimate the safety and efficacy of the administration of active vitamin D and different drugs in the control group. Results: The results of the pairwise meta-analysis revealed that compared with active vitamin D monotherapy, cinacalcet plus active vitamin D did not improve the survival of patients but significantly improved the blood calcium compliance rate [relative risk (RR) =1.82, 95% confidence interval (CI): 1.51–2.21, P